2022
DOI: 10.3389/fpsyg.2022.853830
|View full text |Cite
|
Sign up to set email alerts
|

“Responsible” or “Strange?” Differences in Face Mask Attitudes and Use Between Chinese and Non-East Asian Canadians During COVID-19’s First Wave

Abstract: Early in the COVID-19 pandemic, journalists and scholars noted differences between Asians and North Americans in their support for public mask use. These differences were primarily assumed to be due d to variations in ethnocultural norms and practices. To better ascertain people’s motives for wearing masks and potential cultural differences in these rationales, this comparative, mixed-methods research examines Chinese and non-East Asian Canadians’ mask use attitudes utilizing online group interviews (Study 1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…It's just Asian people wear masks…when you're sick to be polite." (Zhang et al, 2022) Societal attitudes (n = 51). There was a shift in the social acceptability of preventive health behaviours across both smoke-free policy and COVID-19 studies.…”
Section: Political Environment -Facilitates Change and Shifts Perspec...mentioning
confidence: 99%
“…It's just Asian people wear masks…when you're sick to be polite." (Zhang et al, 2022) Societal attitudes (n = 51). There was a shift in the social acceptability of preventive health behaviours across both smoke-free policy and COVID-19 studies.…”
Section: Political Environment -Facilitates Change and Shifts Perspec...mentioning
confidence: 99%
“…This finding is a critical one since the use of NPIs post-vaccination have had mixed policy responses as they been closely associated with socio-cultural freedoms and geographic context [13]. For Asia, some evidence indicates that NPIs such as mask mandates might continue to be practicable, even preferred, despite the relaxations with CVCs, unlike in Western countries where mandates have been dropped, only to be reinstated occasionally as new variants emerge [14][15][16][17]. With models indicating an inevitable steep rise in cases without the continued use of NPIs [12], estimating the appetite for their continuation and identifying nudges to support their use is an area of further investigation [7,8,18].…”
Section: Conditions Under Which Cvcs Are Most Acceptablementioning
confidence: 99%
“…A meta-analysis found that the high use of masks in Asian countries, even after mandates were lifted, is related to the perceived usefulness and necessity of masks by individuals (Leffler et al, 2020). In fact, before COVID-19, wearing masks in Asia is not an uncommon sight during the winter, as masks policies and public health education efforts during the 1918 H1N1, SARS-CoV, and MERS outbreaks helped normalize masks (Ives, 2022;Rich & Hayashi, 2020;Zhang et al, 2022). Hence, communication and education on part of leaders can tremendously impact the public understanding of the need for specific public health measures, thereby positively influencing public compliance during their implementations.…”
Section: Risk Communication and Trust Buildingmentioning
confidence: 99%